Input shape effect on classification performance of raw eeg motor imagery signals with convolutional neural networks for use in brain-computer interfaces - TAÇGIN, ERTUĞRUL (My University, 2023)
EEG signals are interpreted, analyzed and classified by many researchers for use in brain–computer interfaces. Although there are many different EEG signal acquisition methods, one of the most interesting is motor imagery signals. Many different signal processing methods, machine learning and deep learning models have been developed for the classification of motor imagery signals. Among these, Convolutional Neural Network models generally achieve better results than other models. Because the size and shape of the data is important for training Convolutional Neural Network models and discovering the right relationships, researchers have designed and experimented with many different input shape structures. However, no study has been found in the literature evaluating the effect of different input shapes on model performance and accuracy. In this study, the effects of different input shapes on model performance and accuracy in the classification of EEG motor imagery signals were investigated, which had not been specifically studied before. In addition, signal preprocessing methods, which take a long time before classification, were not used; rather, two CNN models were developed for training and classification using raw data. Two different datasets, BCI Competition IV 2A and 2B, were used in classification processes. For different input shapes, 53.03–89.29% classification accuracy and 2–23 s epoch time were obtained for 2A dataset, 64.84–84.94% classification accuracy and 4–10 s epoch time were obtained for 2B dataset. This study showed that the input shape has a significant effect on the classification performance, and when the correct input shape is selected and the correct CNN architecture is developed, feature extraction and classification can be done well by the CNN architecture without any signal preprocessing.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Sinirbilim ve Davranış; SİNİR BİLİMİ; Life Sciences (LIFE); NEUROSCIENCE & BEHAVIOR; NEUROSCIENCES; Genel Sinirbilim; General Neuroscience; brain–computer interface (BCI); classification; deep learning; EEG motor imagery; input shape; raw data; : brain–computer interface (BCI); deep learning; EEG motor imagery; classification; input shape; raw data